Validation of Analytical Methods: A Comprehensive Review - Kumbhare, manoj Ramesh; Surana, Ajaykumar Rikhabchand; Dighe, Pravin Rangnath (Universitas Negeri Semarang, 2023)
Validation of analytical method development is necessary to produce reliable results for regulatory submissions. These techniques are necessary for a variety of tasks, including as testing for quality control release, testing of stability samples, testing of reference materials, and providing information to back up specifications. An important step in the drug discovery process is the use of an analytical method followed by a technique for creating evidence that offers a high level of assurance. Despite the drug's good potency, the lack of a recognised analytical method prevents the drug from being sold. This preserves the drug's quality and safety. This review offers suggestions for several approaches to assure a drug's stability as well as different validation criteria that imitate to different regulatory agencies.